Vous êtes sur la page 1sur 6

# Special products of polynomials

In the previous section we showed you how to multiply binominals. There are a couple of special instances where
there are easier ways to find the product of two binominals than multiplying each term in the first binomial with all
terms in the second binomial.
Look what happens when you square a binomial.

(x+2)2=(x+2)2=
=(x+2)(x+2)==(x+2)(x+2)=
=x2+2x+2x+4==x2+2x+2x+4=
=x2+4x+4=x2+4x+4
=x2+(22x)+22=x2+(22x)+22
This is a pattern that's called the square of a binomial pattern.

(x+y)2=x2+2xy+y2(x+y)2=x2+2xy+y2
(xy)=x22xy+y2(xy)=x22xy+y2
There is another pattern that is good to know. We begin by looking at an example. What happens if we multiply two
binominals where one is a sum of two terms and the other is the different between the same two terms?

(x+5)(x5)=x25x+5x25=x225=x252(x+5)
(x5)=x25x+5x25=x225=x252
This is called the sum and difference pattern.

(x+y)(xy)=x2y2

Square of a Binomial
The square of a binomial is always a trinomial. It will be helpful to memorize these patterns for
writing squares of binomials as trinomials.

(a+b)2=a2+2ab+b2(a+b)2=a2+2ab+b2
(ab)2=a22ab+b2(ab)2=a22ab+b2
Examples:
Square each binomial.

a)(x+4)2a)(x+4)2
(x+4)2=x2+2(x4)+42=x2+8x+16(x+4)2=x2+2(x4)+42=x2+8x+16
b)(2y3)2b)(2y3)2
(2y3)2=(2y)22(2y3)+32=(2y)22(6y)+32
=4y212y+9(2y3)2=(2y)22(2y3)+32=(2y)22(6y)+32=4y212y+9
c)(3p2q2)2c)(3p2q2)2
(3p2q2)2=(3p)22(3p2q2)+(2q2)2=9p22(6pq2)+4q4
=9p212pq2+4q4(3p2q2)2=(3p)22(3p2q2)+(2q2)2
=9p22(6pq2)+4q4=9p212pq2+4q4
If the coefficients of a trinomial ax2+bx+cax2+bx+c satisfy the equation

c=(b2a)2c=(b2a)2,
then the trinomial is the perfect square of the binomial

ax+b2ax+b2.

Example 1:
Factor, if possible.

x214x+49x214x+49
Here, a=1,b=14,andc=49a=1,b=14,andc=49. We have:

(b2a)2=(1421)2=(7)2=49=c(b2a)2=(1421)2=(7)2=49=c
So, the trinomial is a perfect square:

x214x+49=(x7)2x214x+49=(x7)2
You can verify this using FOIL.
Example 2:
Factor, if possible.

9w4+12w2+49w4+12w2+4
Here, a=9,b=12,andc=4a=9,b=12,andc=4. (We can treat w2w2 as xx , and not worry
about the fourth power.)

(b2a)2=(1229)2=(126)2=4=c(b2a)2=(1229)2=(126)2=4=c
So, the trinomial is a perfect square:

9w4+12w2+4=(3w2+2)29w4+12w2+4=(3w2+2)2
This can also be verified using FOIL.

## Finding the Sum and Difference of the Same Two

Terms
When distributing binomials over other terms, knowing how to find the sum and
difference of the same two terms is a handy shortcut. The sum of any two terms
multiplied by the difference of the same two terms is easy to find and even easier to
work out the result is simply the square of the two terms. The middle term just
disappears because a term and its opposite are always in the middle.
If you encounter the same two terms and just the sign between them changes, rest
assured that the result is the square of those two terms. The second term will always be
negative, as in the example,

Example 1: (x 4)(x + 4)
You can use the shortcut to do these special distributions.

The second term will always be negative, and a perfect square like the first term: (4)
(+4) = 16.

## Example 2: (ab 5)(ab + 5)

Try the same easy process multiplying the sum of two terms with their difference
with this slightly more complicated, variable term.

The second term is negative, and a perfect square like the first term: 5 = 25.

## Example 3: [5 + (a b)][5 (a b)]

This example offers you a chance to work through the sum and difference of various
groupings.
The square of 5 = 25
The second term is negative, and a perfect square like the first term:

Square the binomial and distribute the negative sign, which looks like this:

## Multiplying Binomials and Trinomials

Back to Top

Multiplying binomials and trinomials is same as we multiply trinomials. Let us see with the help of
examples how binomials are multiplied by trinomials:

Solved Examples
Question 1: Multiply (x + 3)(x2 + y + 5)
Solution:
(x + 3) (Binomial)
(x2 + y + 5) (Trinomial)
Multiply each term of the binomial by the each term of the trinomial.
(x + 3)(x2 + y + 5) = x(x2 + y + 5) + 3(x2 + y + 5)
= (x * x2+ x * y + 5x) + 3x2+ 3y + 3 * 5
= x3+ xy + 5x + 3x2 + 3y + 15

= x3 + 3x2 + xy + 5x + 3y + 15
Therefore, the product of (x + 3) and (x2 + y + 5) is x3 + 3x2 + xy + 5x + 3y + 15.

## Question 2: Solve (x + y - 3)(y + 5)

Solution:
(x + y - 3) ..........Trinomial
(y + 5)................Binomial
(x + y - 3)(y + 5) = x(y + 5) + y(y + 5) - 3(y + 5)
= xy + 5x + y2 + 5y - 3y - 15
= xy + 5x + y2 + 2y - 15 (Combine like terms)
Therefore, the product of (x + y - 3) and (y + 5) is xy + 5x + y 2 + 2y - 15.